FibonacciN - f(z) = f(z-1) + f(z-2); end y = f(n);

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
function y = FibonacciN(n) f(1) = 1; f(2) = 1; for z = 3:n
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: f(z) = f(z-1) + f(z-2); end y = f(n);...
View Full Document

This note was uploaded on 03/24/2011 for the course PROGRAMMIN 127 taught by Professor Brenda during the Fall '10 term at Rutgers.

Ask a homework question - tutors are online